Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1037/a0038647
|View full text |Cite
|
Sign up to set email alerts
|

Personality change following unemployment.

Abstract: Unemployment has a strongly negative influence on well-being, but it is unclear whether it also alters basic personality traits. Whether personality changes arise through natural maturation processes or contextual/environmental factors is still a matter of debate. Unemployment, a relatively unexpected and commonly occurring life event, may shed light on the relevance of context for personality change. We examined, using a latent change model, the influence of unemployment on the five-factor model of personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(132 citation statements)
references
References 133 publications
5
125
2
Order By: Relevance
“…The finding that job loss significantly increases an individual's openness score contrasts previous findings that identify no change in personality traits after life events such as unemployment, divorce, and marriage (Boyce et al, 2015;Schurer, 2012, 2013;Specht et al, 2011). However, unlike previous studies, we restrict our sample to working individuals without any unemployment experience and focus on an exogenous life event, and therefore, we are able to identify causal effects.…”
Section: Resultscontrasting
confidence: 51%
See 4 more Smart Citations
“…The finding that job loss significantly increases an individual's openness score contrasts previous findings that identify no change in personality traits after life events such as unemployment, divorce, and marriage (Boyce et al, 2015;Schurer, 2012, 2013;Specht et al, 2011). However, unlike previous studies, we restrict our sample to working individuals without any unemployment experience and focus on an exogenous life event, and therefore, we are able to identify causal effects.…”
Section: Resultscontrasting
confidence: 51%
“…Previous studies identified rather small or no changes in individuals' personality traits, while looking at the average stability of personality traits (Boyce et al, 2015;Cobb-Clark and Schurer, 2012;Specht et al, 2011). Average changes in the population analyzed in previous studies may have absorbed strong effects that are valid only for a fraction of the working-age population.…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations